2002
DOI: 10.1556/avet.50.2002.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Equid herpesvirus 1 is neurotropic in mice, but latency from which infectious virus can be reactivated does not occur

Abstract: Equid herpesvirus 1 (EHV-1) is the most common cause of virus-induced abortion in horses. After primary infection the virus becomes latent predominantly in the respiratory tract lymph nodes and the genome can also be detected in the peripheral nervous system. The role of mouse as a feasible model for the establishment of latency and reactivation of EHV-1 was investigated. Intracerebral and intranasal infections of 3-and 17-day-old mice were made and virus replication was confirmed by virus isolation and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In one study, EHV‐1 antigen was demonstrated by indirect immunofluorescence in the trigeminal ganglia of adult mice 2 months after i.n. inoculation (40). Such scattered observations presenting virus in the trigeminal ganglia might be explained by the slight traumatization of the nasal mucosa during the instillation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, EHV‐1 antigen was demonstrated by indirect immunofluorescence in the trigeminal ganglia of adult mice 2 months after i.n. inoculation (40). Such scattered observations presenting virus in the trigeminal ganglia might be explained by the slight traumatization of the nasal mucosa during the instillation procedure.…”
Section: Discussionmentioning
confidence: 99%